Rethinking African Studies: Four Challenges and the Case for Comparative African Studies. Issue 2 (August 2020) - Basedau, Matthias
This article takes stock of the state of African Studies and argues that (1) research on Africa is strongly dominated by outside, non-African, mostly Western views; (2) there is a tendency towards undifferentiated views on "Africa, " which usually concentrate on negative aspects, overlooking progress in many areas; (3) methodologies that focus on causal identification are rarely used; and (4) the field focuses on micro-perspectives while few works examine the big picture and the longue durée . The article then argues that Comparative African Studies, which builds upon the concept of Comparative Area Studies, can address some of these challenges. A pronouncedly comparative perspective would help to systematically combine and contrast "outside" and "inside" perspectives in order to better identify causal relationships and general trends both within Africa and between Africa and other regions. Consequently, African Studies requires more resources and should more effectively engage in multi-disciplinary and mixed-methods research.